2009
DOI: 10.1161/strokeaha.108.531293
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Types, Risk Factors, and Outcome of Stroke in a Developing Country

Abstract: Background and Purpose-Despite increasing burden of stroke in developing countries, population-based data are rare.Through the Trivandrum Stroke Registry, we intend to assess incidence, types, risk factors, and outcome of stroke among urban and rural dwellers of a South Indian community. Methods-We ascertained all first-ever strokes occurring among 741 000 urban and 185 000 rural inhabitants of Trivandrum, Kerala. In addition to Steps 1 and 2 of World Health Organization STEPS Stroke Manual, we used multiple s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
220
2
11

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(256 citation statements)
references
References 22 publications
23
220
2
11
Order By: Relevance
“…Most of these studies reveal diabetes to be an important risk factor for stroke. Diabetes was present in about half of stroke patients in a community based Stroke Registry in Trivandrum, South India [63]. However, one case control study with 201 subjects from a rural tertiary care hospital in Nagpur, central India did not find diabetes to be a statistically significant risk factor for ischemic stroke [64].…”
Section: Cerebrovascular Diseasementioning
confidence: 97%
See 1 more Smart Citation
“…Most of these studies reveal diabetes to be an important risk factor for stroke. Diabetes was present in about half of stroke patients in a community based Stroke Registry in Trivandrum, South India [63]. However, one case control study with 201 subjects from a rural tertiary care hospital in Nagpur, central India did not find diabetes to be a statistically significant risk factor for ischemic stroke [64].…”
Section: Cerebrovascular Diseasementioning
confidence: 97%
“…The average annual incidence rate of stroke in India currently is 145 per 100,000 population [44], which is higher than developed countries. In India 10% to 15% of strokes occur in people aged below 40 years and about 80% of strokes are ischaemic [45] The problem is compounded by poor awareness about warning symptoms and risk factors of stroke amongst Indians [46] Table 2 lists the studies reporting the prevalence of diabetes in people with stroke [47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62]. Most of these studies reveal diabetes to be an important risk factor for stroke.…”
Section: Cerebrovascular Diseasementioning
confidence: 99%
“…48 Various studies in India and Pakistan reported significant incidence of obesity among stroke patients. 35,49 Unique anthropometry and Thinfat phenotype among South Asians, where there is low Basal metabolic index and higher amount of central obesity, are the cardiometabolic risk factors. 50 Abdominal obesity in young, which is more associated with atherosclerosis, hypertension and diabetes, is found to be more common in South Asians than westerners.…”
Section: Obesitymentioning
confidence: 99%
“…The evidence for this, documented in a systematic review initially in 1997, was the catalyst for a marked change in stroke service organisation across the NHS'' [16]. In recent years, multiple activities supporting organised stroke care sprouted in Eastern European and developing countries, enlarging the borders of applied science outside the countries where the knowledge was produced [18,19]. In Italy both regional and scientific society guidelines put emphasis on the implementation of stroke units [20,21].…”
Section: Insight On the Stroke Unit Cochrane Reviewmentioning
confidence: 99%